Neuromuscular Taping Decompression Techniques Fail to Prevent Muscle Damage After Eccentric Movement Activity - Muhammad Zainal Arifin; Bambang Purwanto; Damayanti Tinduh (Journal Physical Education, Health and Recreation, 2020)
Eccentric activity is a type of activity facilitated by the addition of one or several muscles and often leaves the effects of pain even damage to muscle cells. The study aimed to determine the effect of the application of neuromuscular taping decompression techniques to muscle damage after eccentric movement activity. The type of research conducted is experimental research with post test only with control group design. Fourteen samples were selected from non-athlete populations at SMAN 1 Driyorejo based on consecutive sampling techniques and then divided into two groups randomly. Intervention of neuromuscular taping decompression techniques was given to the treatment group before performing eccentric movement activities. The elbow shoulder-extension flexion movement by holding 9% weight in 20 seconds was chosen as the protocol of eccentric movement activity. Measuring indicators of muscle damage using a serum Ck muscle examination 6 hours after rest. The results of the independent t-test showed no significant difference in the variable of muscle damage (p> 0.05). It was concluded from this study that the neuromuscular taping decompression technique failed to prevent muscle damage after eccentric movement activity.